1986
DOI: 10.1111/j.1471-4159.1986.tb00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain α‐Ketoglutarate Dehydrogenase Complex: Kinetic Properties, Regional Distribution, and Effects of Inhibitors

Abstract: The substrate and cofactor requirements and some kinetic properties of the alpha-ketoglutarate dehydrogenase complex (KGDHC; EC 1.2.4.2, EC 2.3.1.61, and EC 1.6.4.3) in purified rat brain mitochondria were studied. Brain mitochondrial KGDHC showed absolute requirement for alpha-ketoglutarate, CoA and NAD, and only partial requirement for added thiamine pyrophosphate, but no requirement for Mg2+ under the assay conditions employed in this study. The pH optimum was between 7.2 and 7.4, but, at pH values below 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
2
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(167 citation statements)
references
References 62 publications
2
160
2
3
Order By: Relevance
“…Consistent with previous investigations (Sims, 1990), the specific activities of mitochondrial en zymes measured in the present study were two-to threefold greater than values reported previously (Lai and Cooper, 1986;Mizuno et aI., 1987;Elnageh and Gaitonde, 1988) for brain mitochondria isolated using alternative preparative procedures. As the isolated mitochondrial population is likely to in clude organelles from both neuronal and glial cells, no conclusions can be reached as to the cellular location of the observed changes in the dorsolateral striatum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous investigations (Sims, 1990), the specific activities of mitochondrial en zymes measured in the present study were two-to threefold greater than values reported previously (Lai and Cooper, 1986;Mizuno et aI., 1987;Elnageh and Gaitonde, 1988) for brain mitochondria isolated using alternative preparative procedures. As the isolated mitochondrial population is likely to in clude organelles from both neuronal and glial cells, no conclusions can be reached as to the cellular location of the observed changes in the dorsolateral striatum.…”
Section: Discussionsupporting
confidence: 92%
“…The activity of a-ketoglutarate dehydrogenase in mito chondria was determined spectrophotometric ally as de scribed by Lai and Cooper (1986). Only one cycle of freezing and thawing was required to obtain maximum activity.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Increased brain lactate correlated with worsening encephalopathy and intracranial hypertension in experimental models [92] and [121], and it was due to increased de novo synthesis from circulating glucose. This observation suggests decreased oxidation of pyruvate [92], in accordance with inhibition of alpha-ketoglutarate dehydrogenase and stimulation of the glycolytic enzyme phosphofructokinase by ammonia in vitro [122] and [123]. The effects of hypothermia (32-33 °C) on brain glucose metabolism were studied by Jalan et al in patients with ALF and uncontrolled ICP [80].…”
Section: Brain Glucose Metabolismmentioning
confidence: 95%
“…It has also been demonstrated that alanine is elevated in the hyperammonemic brain (Hilgier et al, 1999;Mans et al, 1994;Swain et al, 1992) and more recently in rats with ALF using nuclear magnetic resonance (NMR) spectroscopy (Chatauret et al, 2003). Increased lactate and alanine production indirectly suggest that anaerobic pathways (increased glycolytic activity) may be stimulated to compensate for a decreased pyruvate oxidation (due to ammonia inhibition on the enzyme alpha-ketoglutarate dehydrogenase in the tricarboxylic acid cycle (Lai and Cooper, 1986)) and maintain ATP production. Furthermore, decreased concentrations of the neuronal marker molecule N-acetylaspartate (NAA) have been demonstrated in frontal cortex of rats in coma stages of HE as a result of ALF, reflecting neuronal mitochondrial dysfunction (Chatauret et al, 2003).…”
Section: The Pathophysiology Of Hypothermia-effect On the Brainmentioning
confidence: 99%